What does the guitalele like sound: Guitar or ukelele? An application of the K-means cluster method - Juan-Francisco Fuentealba; Sebastián Michea (AIP Advances)
This study embarks on a novel investigation into the guitalele’s acoustic properties, aiming to delineate its sound profile relative to its progenitors—the guitar and the ukulele. Leveraging a multifaceted approach that combines subjective perception surveys with objective frequency response analysis, we scrutinize the guitalele’s harmonic spectrum to elucidate its unique tonal identity. The experimental setup involved precise recordings of each instrument’s output across a range of notes, followed by sophisticated audio analysis techniques including Fourier transform to dissect the harmonic components and cross-correlation functions to identify representative sound pulses. In addition, advanced statistical methods, specifically K-means clustering, were applied to the harmonic data, offering a quantitative perspective on the guitalele’s sound classification relative to the guitar and ukulele. The investigation reveals that the guitalele embodies a complex acoustic blend, mirroring the guitar’s harmonic richness while retaining timbral characteristics reminiscent of the ukulele. Despite its closer visual and geometric alignment with the ukulele, the guitalele’s sound is predominantly influenced by the guitar, suggesting a hybrid sonic identity that transcends a simple binary classification. This unique amalgamation of sound properties suggests that the guitalele offers musicians a distinct voice that leverages the qualities of both instruments while establishing its own acoustic signature.